Investigation On PVT Performance Under Low Intensity Irradiation - Hashim, Muhammad Hazwan (Universiti Sains Malaysia, 2017)
This project is focused on modeling and analyzing photovoltaic thermal water collector. PV solar panel with the solar thermal collector and without thermal collector will be presented and analyzed. This project used water as the coolant of the PV solar panel. Naturally ventilated panels and water cooled panels can provide high efficiency. The first objective of this project is to build PVT water collector and analyzing the model. The second objective of the project is to investigate whether a PV solar panel with thermal has high output than PV solar panel without or not. Microcontroller data acquisition was built to measure the data from the PVT system. All the electrical parameter will be saved on micro SD card for every 5 minutes using data logger developed using Arduino. The data Solar panel testing is conducted to observe the I-V characteristics of solar panel for both PV with and without a thermal collector. System testing is conducted within 5 hours to obtain output current, output voltage and maximum output power of both conditions of PV solar panel. Both performance of PV solar panel with and without thermal collector is compare analyzed. The result from I-V characteristics shown open circuit voltage increase about 4% and short circuit decrease about 2%. The result from system testing shown output power increase about 6% and temperature of solar panel decrease about 6% when water thermal collector have been used as a cooling system.